Does Higher Pay Increase Vulnerability to the Motherhood Penalty? Challenges for Indonesian Working Women - Kadek Swarniati; Diahhadi Setyonaluri (MUWAZAH : jurnal kajian gender, 2024)
The “motherhood penalty” refers to the negative impact that becoming a mother has on women's overall economic outcomes. This study aims to determine if the severity of this penalty varies for employed and self-employed women across different income levels (poor, middle, and high). Understanding these variations can help policymakers create tailored support systems to promote gender equality and address specific challenges faced by each group. This research fills a gap by examining the extent of the motherhood penalty across women with different incomes and employment statuses. It uses ordinary least squares (OLS) regression on pooled data from the Indonesia Family Life Survey (IFLS) 2000–2014, combining data from 2000, 2007, and 2014 to account for historical economic changes and unique child ownership. The IFLS provides an eight-year work history, crucial for controlling the motherhood penalty mechanism from the forgone experience phase, a feature absent in other surveys. The findings reveal that, compared to childless women, employed mothers earn the least regardless of income level, with a woman's income decreasing as the number of children increases. However, in low-, middle-, and high-paid jobs, only high-paid working mothers experience significantly lower wages compared to their childless counterparts. Self-employed women are less likely to face the motherhood penalty. These results highlight the need for policy interventions to support employed mothers, particularly those in high-income brackets, while recognizing that self-employed women do not experience the same negative financial effects. The study concludes with policy recommendations for decision-makers and stakeholders to address these issues.